2020
DOI: 10.1158/1078-0432.ccr-20-0777
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of IL7 and CCL21 Increases Efficacy of CAR-T Cells in Solid Tumors without Requiring Preconditioned Lymphodepletion

Abstract: There is limited success in using chimeric antigen receptor (CAR) T cells to treat solid tumors. One of the major reasons is the suppressive tumor microenvironment that impairs the infiltration, expansion and persistence of CART cells in tumor tissues. In this study, we engineered CLDN18.2 specific CART cells to co-express cytokines IL-7 and CCL21 (7×21 CART). Our studies indicated that IL-7 and CCL21 can enhance the survival of CART cells and infiltration of T cells and dendritic cells in tumor tissues. 7×21 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 48 publications
1
66
0
Order By: Relevance
“…Recent studies demonstrated that it is possible to co-express multiple cytokines in the same CAR T-cell. For example, Luo et al (2020) engineered CAR T-cells to produce IL-7 and CCL21 and demonstrated that this combination improved survival and infiltration of CAR T-cells in solid tumors in vivo, without requiring preconditioned lymphodepletion [ 208 ]. NCT04833504 is a clinical trial recently completed in which CD19 + CAR T-cells expressing IL-7 and CCL19 were tested in patients with relapsed or refractory B-cell lymphoma, however the results have not yet been reported.…”
Section: Strategies To Improve Car T-cell Persistence and Potencymentioning
confidence: 99%
“…Recent studies demonstrated that it is possible to co-express multiple cytokines in the same CAR T-cell. For example, Luo et al (2020) engineered CAR T-cells to produce IL-7 and CCL21 and demonstrated that this combination improved survival and infiltration of CAR T-cells in solid tumors in vivo, without requiring preconditioned lymphodepletion [ 208 ]. NCT04833504 is a clinical trial recently completed in which CD19 + CAR T-cells expressing IL-7 and CCL19 were tested in patients with relapsed or refractory B-cell lymphoma, however the results have not yet been reported.…”
Section: Strategies To Improve Car T-cell Persistence and Potencymentioning
confidence: 99%
“…It was found that the secretion of cytokine IL-7 and chemokine CCL19 could promote the infiltration of T cells and dendritic cells (DC) in tumor tissue, reduce T cell depletion, and improve the anti-tumor activity of CAR-T. 69 In addition, IL-7 and CCL21 also significantly improve the proliferation and chemotaxis of CAR-T cells, enhancing the survival and infiltration of CAR-T and DC; besides, CCL21 could inhibit tumor angiogenesis. 70 The modification of IL-8 receptor CXCR1 or CXCR2 significantly enhanced the migration and persistence of CAR-T cells in tumors. 71 CAR-T cells expressing CXCR2 modified by integrin αvβ6-CAR migrated more effectively to tumor cells producing IL-8 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of both IL-7 and CCL19 increased intra-tumoral infiltration of CAR T cells, endogenous T cells, and DCs, which achieved complete regression of established solid tumors and led to the formation of a T cell memory response via epitope spreading. CAR T cells engineered to express IL-7 with CCL19 or CCL21 also had improved antitumor activity due to enhanced CAR T cell proliferation and chemotaxis (98). These studies have been translated into clinical trials to evaluate the safety and efficacy of IL-7 and CCL19 expressing CAR T cells against lymphoma, multiple myeloma, and solid tumors (Table 1).…”
Section: Interleukinmentioning
confidence: 99%